Effectiveness of psychosocial interventions among family caregivers of people with schizophrenia in China: a systematic review of randomized controlled trials - Zou, Wen Yuan; Japar, Salimah; Rajen Durai, Ruthpackiavathy; Liang, Guang Ming; Ma, Qian Cheng (Springer, 2025)
Family caregivers of individuals with schizophrenia frequently experience both significant caregiving burdens and psychological challenges such as anxiety and depression, highlighting the critical need to explore effective psychosocial interventions. This study aims to systematically review the effectiveness of psychosocial interventions for family caregivers of individuals with schizophrenia in China. A comprehensive literature search was conducted across four English databases (PubMed, Web of Science, CINAHL, CENTRAL) and two Chinese databases (WANFANG, CNKI), including studies published from January 1, 2000, to August 1, 2025. The inclusion criteria focused on family caregivers of individuals with schizophrenia in China, with psychosocial interventions as the primary exposure, and caregiver-related outcomes (such as caregiver burden, anxiety, depression, etc.) as primary endpoints. Only randomized controlled trials (RCTs) were considered. A total of 918 records were retrieved, and 11 RCTs were ultimately included in the review, 5 from mainland China and 6 from Hong Kong. The findings demonstrate that psychosocial interventions have a positive impact on alleviating caregiver burden, improving mental health, enhancing positive psychological states, increasing social support, and improving quality of life and life satisfaction. This review suggests that psychosocial interventions may offer potential benefits for family caregivers of individuals with schizophrenia in China. However, due to the limited quality of the available evidence, these findings should be interpreted with caution. Further high-quality, standardized RCTs are needed to validate the efficacy of these interventions and assess their long-term stability.